Energy availability during training camp is associated with signs of overreaching and changes in performance in young female cross-country skiers - Kettunen Oona; Ihalainen Johanna K.; Ohtonen Olli; Valtonen Maarit; Mursu Jaakko; Linnamo Vesa (Sciendo, 2021)
Study aim: The aim of this study was to evaluate if young female skiers meet their energy and macronutrient requirements, and how energy availability (EA) and macronutrient intake affects their performance during an intensive training camp.